Research of pigments of blue-green algae spirulina platensis for practical use in confectionery technology - T. K. Kalenik (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2019)
The article presents a study of the process of isolation of natural blue pigment – phycocyanin from the biomass of blue-green algae Spirulina platensis by water extraction, followed using its water solution as a natural food colorant in the production of milk chocolate. Recently, modern food enterprises are pursuing their policy towards expanding the range of products, which is closely related to the increasing needs of the population in food of a new kind. One of the solutions to this problem is the use of food additives of both natural and synthetic origin. Among the similar components widespread found dyes synthetic origin, which have high coverage rates and relatively low cost. However, many of the permitted in our country synthetic food dyes are banned in several developed countries as potentially dangerous to health. Synthetic dyes of red, yellow and green color have many natural analogues – carotenoids, lutein, chlorophyll, etc., except for the blue dye, the analogue of which is only anthocyanins, which are unstable depending on the pH conditions. In this article were identified phycobiliproteins and chlorophyll a in a water extract of spirulina. The mass concentration of phycobiliproteins and chlorophyll a was determined by spectrophotometric method before and after the addition of ammonium sulfate. A comparative analysis of the effect of fractionation (salting out) on the degree of purification of the phycocyanin solution. Presented and described the technological scheme of extraction of phycocyanin which allows to use it in food technologies as an extract or a dry powder. Established the concentration of phycocyanin extract from blue-green algae spirulina to produce milk blue chocolate. Determined organoleptic and hygienic characteristics of the finished product